Effect of Online Marketing (E-Commerce) Activities to the Advantages of Competing Traditional Culinary Products in South Sulawesi - Syahrial; Lily Dianafitry Hasan; Muhammad Musawantoro; Faisal Akbar Zainal (Politeknik Pariwisata Makassar, Indonesia, 2020)
This study aims to determine whether the method of Online marketing (Ecommerce) influences competitive advantage This type of research is quantitative descriptive with statistical data analysis, where the population and sample are all traditional culinary industries in South Sulawesi especially in Makassar, Pare-Pare, Bulukumba and Bantaeng. This research was conducted by distributing questionnaires to 80 respondents. Samples were taken by puposive sampling. Data analysis was performed using regression analysis The results of this study indicate that the influence of online methods (Ecommerce) on competitive advantage is partially significant.